ASSESSING SUBJECTIVE BURDEN AND QUALITY OF LIFE IN FAMILY CAREGIVERS OF OLDER ADULTS - Patrick Alexander Wachholz; Patricia Ribeiro Mattar Damiance (Brazilian Society of Geriatrics and Gerontology, 2021)
OBJECTIVE: To evaluate subjective burden and perceived quality of life in primary caregivers who care for older adults at home. Caregivers were followed up in a pilot support group. The study also sought to describe the experience of encouraging dialogue and interaction within this group. METHODS: This quanti-qualitative study was limited to nine family caregivers. Data were collected using the following instruments: the World Health Organization Quality of Life abbreviated version, the Zarit caregiver burden interview, the family APGAR questionnaire, the Hospital Anxiety and Depression Scale, the Katz index of independence in activities of daily living, and the Neuropsychiatric Inventory. Dialogue and interaction in the support group meetings was encouraged through guiding questions. RESULTS: The family caregivers, mostly women with low education, were responsible for older patients who were functionally dependent and had a low frequency and intensity of neuropsychiatric symptoms. The caregivers actively participated in the pilot group. They reported a mild subjective burden and did not present depressive symptoms. They had borderline anxiety symptoms and scores above 60 for all quality of life domains, in addition to good family functionality. CONCLUSIONS: The participants in this pilot group had a mild subjective burden, good perceived quality of life, and showed interest in a caregiver support group. Such groups could be a complementary and instrumentalizing practice in home care and could contribute to a lower caregiver burden and caregiver anxiety, improving their perceived quality of life related to the psychological and social relationship domains.